2016
DOI: 10.1038/aps.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated bilirubin elevation impairs the function and expression of breast cancer resistance protein (BCRP) at the blood-brain barrier in bile duct-ligated rats

Abstract: Aim: Liver failure is associated with dyshomeostasis of efflux transporters at the blood-brain barrier (BBB), which contributes to hepatic encephalopathy. In this study we examined whether breast cancer resistance protein (BCRP), a major efflux transporter at the BBB, was altered during liver failure in rats. Methods: Rats underwent bile duct ligation (BDL) surgery, and then were sacrificed after intravenous injection of prazosin on d3, d7 and d14. The brains and blood samples were collected. BCRP function at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…The effects of unconjugated bilirubin (UCB), cholic acid (CA), deoxycholic acid (DCA), lithocholic acid (LCA), chenodeoxycholic acid (CDCA), and ursodeoxycholic acid (UDCA) on P-GP function and expression were investigated in HCMEC/D3 and MDCK-BCRP (MDCK type II cells transfected with human BCRP) cells. In brief, sub-confluent (80%) cells were incubated with medium containing different concentrations of UCB (0, 10, or 25 μM) and bile acids (0, 10, or 100 μM) for 24 h. The concentrations of UCB and individual bile acids were chosen based on previous studies ( Komori et al, 2014 ; Liu et al, 2014 ; Xu et al, 2016 ). It is noted that the data from a MTT study demonstrated that cell viability was not impaired by these agents at the tested concentrations ( Figures 2A,B ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of unconjugated bilirubin (UCB), cholic acid (CA), deoxycholic acid (DCA), lithocholic acid (LCA), chenodeoxycholic acid (CDCA), and ursodeoxycholic acid (UDCA) on P-GP function and expression were investigated in HCMEC/D3 and MDCK-BCRP (MDCK type II cells transfected with human BCRP) cells. In brief, sub-confluent (80%) cells were incubated with medium containing different concentrations of UCB (0, 10, or 25 μM) and bile acids (0, 10, or 100 μM) for 24 h. The concentrations of UCB and individual bile acids were chosen based on previous studies ( Komori et al, 2014 ; Liu et al, 2014 ; Xu et al, 2016 ). It is noted that the data from a MTT study demonstrated that cell viability was not impaired by these agents at the tested concentrations ( Figures 2A,B ).…”
Section: Methodsmentioning
confidence: 99%
“…We once reported that both acute and chronic liver failure induced by thioacetamide (TAA) downregulated P-GP function and expression, and upregulated MRP2 function and expression at the BBB of rats ( Jin et al, 2013 ). Similarly, both function and expression of BCRP at the BBB of rats were decreased by ALF or bile duct ligation, leading to increases in brain distribution of prazosin ( Li et al, 2016 ; Xu et al, 2016 ). These results indicated that the altered function of ABC transporters at the BBB by ALF might affect the brain distribution, CNS activity, and toxicity of their substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence [ 26 , 27 , 28 , 53 , 72 , 73 , 74 , 75 ] has demonstrated that liver failure altered the expression and function of ABC transporters at the BBB, and that the alterations were dependent on types of the developed liver failure and the species of ABC transporters. ALF rats were developed using intraperitoneal injection of thioacetamide (TAA) (300 mg/kg) for two days with a 24-h interval [ 26 , 53 ].…”
Section: Alterations In Expression and Function Of Abc Transportermentioning
confidence: 99%
“…Furthermore, incubation with BDL rat serum significantly decreased BCRP function and protein levels in both HCMEC/D3 and MDCK-BCRP cells, indicating that some abnormal components in BDL rat serum might impair BCRP function at the BBB. BDL rats exhibited significant elevations of UCB and bile acids [ 72 ]. In vitro data showed that only incubation with 25 μmol/L UCB significantly increased the uptake of prazosin, and downregulated the expression of BCRP protein in HCMEC/D3 and MDCK-BCRP cells.…”
Section: Alterations In Expression and Function Of Abc Transportermentioning
confidence: 99%
See 1 more Smart Citation